(untitled) (Applied Biological Research, 2024)
Papaya is one of the important nutrient rich tropical fruit that is preferred and cultivated almost in majority of the states of India. Choice of variety, proper nutrition and disease management are the key operations for successful commercial papaya cultivation. Micronutrient deficiency starting from the early stage of growth can cause poor growth and yield reduction. Thus a potted plant experiment was conducted to study the influence of zinc and boron as foliar application on seedling growth of papaya. The experiment was laid out in a completely randomized design with nine treatments comprising of zinc sulphate @ 0.2 and 0.4%, and borax @ 0.2 and 0.4% and their combinations along with a control treatment (distilled water spray). The seedlings were raised in polythene bags filled with growing media (soil: sand: FYM @ 4:2:1) and sprayed with the micronutrients as per treatment, adjusting neutral pH at 15 day’s interval after germination. The application of ZnSO4 @ 0.4% + borax @ 0.2% improved seedling growth of papaya in terms of height, girth, number of leaves and leaf size. Also, the fresh and dry weights of shoot and root also showed significant improvement. Thus the foliar application of ZnSO4 @ 0.4% + borax @ 0.2% can be recommended for better seedling growth of papaya.